About iCGPA - UMP, LIB (The New Straits Times Press (M) Bhd., 2017)
The iCGPA is an integrated mechanism introduced in 2015 by the Ministry of Higher Education [MOHE] to achieve its vision of producing holistic, entrepreneurial and balanced graduates, in line with the Malaysia Education Blueprint 2015-2025 [Higher Education].